2012
DOI: 10.1088/1367-2630/14/4/043043
|View full text |Cite
|
Sign up to set email alerts
|

The glass to superfluid transition in dirty bosons on a lattice

Abstract: We investigate the interplay between disorder and interactions in a Bose gas on a lattice in the presence of randomly localized impurities. We compare the performance of two theoretical methods, namely the simple version of multi-orbital Hartree-Fock and the common Gross-Pitaevskii approach, and show how the former gives a very good approximation to the ground state in the limit of weak interactions, where the superfluid fraction is small. We further prove rigorously that for this class of disorder the fractal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…This statement concerns the usual thermodynamic limit. We note that other limiting regimes are possible, corresponding to mean-field type interactions, where both BEC and superfluidity can prevail at zero temperature [30,50] (see also [8,29,54] for related results). The proof of theorem 2.4 will be given in section 4.…”
Section: Absence Of Superfluiditymentioning
confidence: 79%
“…This statement concerns the usual thermodynamic limit. We note that other limiting regimes are possible, corresponding to mean-field type interactions, where both BEC and superfluidity can prevail at zero temperature [30,50] (see also [8,29,54] for related results). The proof of theorem 2.4 will be given in section 4.…”
Section: Absence Of Superfluiditymentioning
confidence: 79%
“…In recent years the interplay between interactions and disorder in many body systems has been studied in many works, both theoretically and experimentally. It is not the intention here to give a review of the subject but we mention the references [12][13][14][15][16][17][18][19][20][21][22][23][24] as a representative sample. In [25] (see also [26]) a one-dimensional model of an interacting Bose gas was studied and it was shown that complete BEC in the ground state may survive a strong random potential in an appropriate limit.…”
Section: Introductionmentioning
confidence: 99%
“…By pinning a secondary type of atoms in an optical potential we obtain the disorder with binary (or Bernoulli) distribution. Such proposal, originating from the work of Gavish and Castin [29], has been frequently discussed theoretically [30][31][32][33]36], and only recently implemented experimentally [37] (note that in the early papers [38] the impurities were mobile). This is the type of disorder we consider in this paper.…”
Section: Introductionmentioning
confidence: 99%